THE ANALISIS EFFECT OF AWARENESS OF THE TAXPAYER AND SERVICE TAX AUTHORITIES ON TAX COMPLIANCE (CASE RESEARCH ON NORTH KARAWANG PRIMARY TAX SERVICES OF 2018) - Yanti; Maemunah, Mumun; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research was to determine the effect of awareness of the tax payer and service tax authorities on tax compliance. This research was conducted at the Pratama Karawang North Tax Service Office in 2018. This research uses a quantitative approach. The sample is taken by convience sampling technique, with a sample size of 100 respondents. Data collection methods related to research use question naire methods in the form of statements. The partial test results (t) show that the awareness of the tax payer and service tax authorities at the Pratama Karawang North Tax Service Office in 2018 have an effect on Taxpayer Compliance. Simultaneous Test Results (F) show that all independent variables have a joint effect on the dependent variable.